Late-time Radio Brightening and Emergence of a Radio Jet in the Changing-look AGN 1ES 1927+654 - Eileen T. Meyer; Sibasish Laha; Onic I. Shuvo; Agniva Roychowdhury; David A. Green; Lauren Rhodes; Amelia M. Hankla; Alexander Philippov; Rostom Mbarek; Ari laor; Mitchell C. Begelman; Dev R. Sadaula; et al. (The Astrophysical Journal Letters)
We present multifrequency (5–345 GHz) and multiresolution radio observations of 1ES 1927+654, widely considered one of the most unusual and extreme changing-look active galactic nuclei (CL-AGNs). The source was first designated a CL-AGN after an optical outburst in late 2017 and has since displayed considerable changes in X-ray emission, including the destruction and rebuilding of the X-ray corona in 2019–2020. Radio observations prior to 2023 show a faint and compact radio source typical of a radio-quiet AGN. Starting in 2023 February, 1ES 1927+654 began exhibiting a radio flare with a steep exponential rise, reaching a peak 60 times previous flux levels, and has maintained this higher level of radio emission for over a year to date. The 5–23 GHz spectrum is broadly similar to gigahertz-peaked radio sources, which are understood to be young radio jets less than ∼1000 yr old. Recent high-resolution Very Long Baseline Array observations at 23.5 GHz now show resolved extensions on either side of the core, with a separation of ∼0.15 pc, consistent with a new and mildly relativistic bipolar outflow. A steady increase in the soft X-ray band (0.3–2 keV) concurrent with the radio may be consistent with jet-driven shocked gas, though further observations are needed to test alternate scenarios. This source joins a growing number of CL-AGNs and tidal disruption events that show late-time radio activity, years after the initial outburst.